Identifying Critical Organizational Management Issues to Confirm Baldrige Framework 2023-2024 Change Items in a Systematic Review - Lusdiono, Andi; Noer, Lissa Rosdiana (Universitas Syiah Kuala, 2025)
This research aims to identify and analyze the critical issues in organizational management from 2021 to 2024 and to assess their alignment with the updates in the 2023-2024 edition of the Baldrige Excellence Framework (BEF). By systematically reviewing management practices, this study maps the evolution and relevance of critical issues such as organizational agility, sustainability, digital transformation, and workforce retention. Cluster analysis reveals significant correlations between these management trends and the updated elements of BEF, suggesting that the frameworks revisions are well-founded on contemporary management challenges. The research supports the hypothesis that modern management practices, particularly in sustainability and digital innovation, have a direct impact on operational excellence and align closely with BEFs new emphasis on adaptability and technological integration.